Bioorthogonal Catalysis: A General Method To Evaluate Metal-Catalyzed Reactions in Real Time in Living Systems Using a Cellular Luciferase Reporter System - Hsu, Hsiao-Tieh; Trantow, Brian M; Waymouth, Robert M; Wender, Paul A (Bioconjugate chemistry, 2016)
The development of abiological catalysts that can function in biological systems is an emerging subject of importance with significant ramifications in synthetic chemistry and the life sciences. Herein we report a biocompatible ruthenium complex [Cp(MQA)Ru(C3H5)]+PF6 – 2 (Cp = cyclopentadienyl, MQA = 4-methoxyquinoline-2-carboxylate) and a general analytical method for evaluating its performance in real time based on a luciferase reporter system amenable to high throughput screening in cells and by extension to evaluation in luciferase transgenic animals. Precatalyst 2 activates alloc-protected aminoluciferin 4b, a bioluminescence pro-probe, and releases the active luminophore, aminoluciferin (4a), in the presence of luciferase-transfected cells. The formation and enzymatic turnover of 4a, an overall process selected because it emulates pro-drug activation and drug turnover by an intracellular target, is evaluated in real time by photon counting as 4a is converted by intracellular luciferase to oxyaminoluciferin and light. Interestingly, while the catalytic conversion (activation) of 4b to 4a in water produces multiple products, the presence of biological nucleophiles such as thiols prevents byproduct formation and provides almost exclusively luminophore 4a. Our studies show that precatalyst 2 activates 4b extracellularly, exhibits low toxicity at concentrations relevant to catalysis, and is comparably effective in two different cell lines. This proof of concept study shows that precatalyst 2 is a promising lead for bioorthogonal catalytic activation of pro-probes and, by analogy, similarly activatable pro-drugs. More generally, this study provides an analytical method to measure abiological catalytic activation of pro-probes and, by analogy with our earlier studies on pro-Taxol, similarly activatable pro-drugs in real time using a coupled biological catalyst that mediates a bioluminescent readout, providing tools for the study of imaging signal amplification and of targeted therapy.